Pengaruh Current Ratio Dan Debt to Equity Ratio terhadap Nilai Perusahaan pada Industri Sub Sektor Semen yang Terdaftar di Bursa Efek Indonesia Periode 2016-2020 - Izzaty Robbany (Universitas Batanghari Jambi, 2021)
This research is the research method used by researchers, namely quantitative descriptive analysis method.This Study uses multiple linear analysis and hypothesis testing. Based on multiple regression analysis, it is known that Y = (1,370) + 0,151 X1 + 0,206 X2. The results of multiple linear regression analysis show the coefficient of determination (R Square) of 25,4%, while the remaining 74,6% is influenced by other variables outside the study. The test results show that simultaneously the variables Current Ratio, Debt to Equity Ratio,have a significant effect on Company Value. This is indicated by the calculated F is greater than the F table (4,591 > 3,35) so that Ho is rejected and Ha is accepted, meaning that there is a significant influence between independent (x) on the influence variable (y). Partially Current Ratio and Debt to Equity Ratio has a significant effect on Company Value.